GE_GERICHTE P/6511/2024 vom 17. Februar 2025 - GE Cour de justice (2025)
LÉSÉ;DOMMAGE DIRECT;GESTION DÉLOYALE;FAUX INTELLECTUEL DANS LES TITRES;FAUX TÉMOIGNAGE | CPP.115; CPP.118; CP.158; CP.251; CP.307